The identification Mycobacterium tuberculosis genes that modulate long term survival in the presence of rifampicin and streptomycin - Johana E. Hernández Toloza; Ye Xu; Tom A. Mendum; Bianca Sica Siedler; Rosalyn Casey; Huihai Wu; Kerstin Williams; Suzanne Hingley-Wilson; Johnjoe McFadden (Scientific Reports)
Abstract In 2023, Mycobacterium tuberculosis (Mtb) caused 10.6 million new tuberculosis cases and 1.3 million deaths. The WHO proscribed treatment is not always successful, even when strains were sensitive to the antibiotics.as clinical Mtb populations contain phenotypically tolerant subpopulations, termed persisters. Here a Mtb transposon library was challenged with rifampicin (RIF) and streptomycin (STM) under conditions designed to identify genes that modulate persister frequency. Mutants with reduced survival in RIF were predominantly in genes associated with membrane integrity e.g. arabinogalactan assembly genes cpsA/lytR/Psr, whilst for STM, reduced survival was associated with toxin/antitoxin genes. Some mutations enhanced survival. For RIF these included the methyl citrate cycle genes prpC, prpD and prpR, and the trkA-C K+ uptake system genes ceoB and Rv2690, and for STM, the resistance associated gene, gidB, and anion-transport genes Rv3679c and Rv3680c. Few genes overlapped the RIF and STM selections, demonstrating that survival mechanisms were antibiotic-specific. Directed deletions of ΔprpD and ΔfadE5 confirmed their predicted enhanced and reduced RIF fitness respectively. The study identified genes that modulate not only persister frequency but also resistance and tolerance, and demonstrates that the mechanisms that produce these phenotypes are diverse and antibiotic-specific.